Hadith in Cakrawala al-Qur'an by Yunahar Ilyas: A Study on Quotations and Authenticity of Transmition - Husna, Jannatul; Awaled, Muhammad Ghofi; Shamsu, Lilly Suzana binti (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Incorporating hadith into the interpretation of the Quran is essential. One of Indonesian Muslims' favourite thematic tafsir books is Cakrawala al-Qur'an by Yunahar Ilyas. This article aims to provide a comprehensive introduction to the author's intellectual biography, the methodology for quoting hadith, and the process of verifying the authenticity of the hadith used to support the interpreter's arguments. This study employs qualitative research methods, specifically using documentation and interviews for data collection. The primary reference for this work is Cakrawala al-Qur'an, published by Itqan Publishing in 2015. Through document analysis, significant insights are uncovered regarding Yunahar Ilyas' expertise, methodology, and the quality of the hadith quoted. The study concludes that Yunahar Ilyas is a highly influential expert in Quranic interpretation and sciences in Indonesia. When citing hadith, he employed four methods, with the most common being the inclusion of the hadith without the sanad but mentioning the mukharrij (collector of hadith) in the translation. Of the nine hadiths analysed, three were critically reviewed: one was found to be fake (maudhu'), one was classified as weak (daif), and one as good (hasan). Despite their varying levels of authenticity, these three hadith texts align with the essence of the Quran, other hadiths, logical reasoning, and historical facts.